2022
DOI: 10.3389/fnhum.2021.771553
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Improves Memory Performance in Older Adults: A Narrative Review of Evidence and Possible Mechanisms

Abstract: Graphical AbstractExercise, neurotransmitters, growth factors, myokines, and potential effects on the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 255 publications
(292 reference statements)
2
28
0
Order By: Relevance
“…Regular exercise increased irisin expression in all tissues analyzed compared to sedentary inactivity (Belviranli and Okudan, 2018). Recent studies have also shown that irisin is associated with improved neurocognitive performance in older adults and plays a key role in the facilitative effects of exercise on learning and memory (Babaei and Azari, 2021). More importantly, in a 2021 study, Colaianni et al examined a series of patients undergoing total hip or knee arthroplasty.…”
Section: Irisin and Agingmentioning
confidence: 99%
“…Regular exercise increased irisin expression in all tissues analyzed compared to sedentary inactivity (Belviranli and Okudan, 2018). Recent studies have also shown that irisin is associated with improved neurocognitive performance in older adults and plays a key role in the facilitative effects of exercise on learning and memory (Babaei and Azari, 2021). More importantly, in a 2021 study, Colaianni et al examined a series of patients undergoing total hip or knee arthroplasty.…”
Section: Irisin and Agingmentioning
confidence: 99%
“…123 Therefore, the protective effects of physical exercise may result from several mechanisms, including not only boosting brain function through myokines and other signals eliciting plastic changes in the hippocampus and other brain areas but also by increasing cerebral blood flow, improving glymphatic drainage, and reducing metabolic and vascular risk factors. 124 For example, exercise-induced myokines, hepatokines (such as FGF1 and IGF1), and adipokines (such as adiponectin) not only promote BDNF signaling and hippocampal neurogenesis but also have insulin-sensitizing, antidiabetic, anti-inflammatory, and antiatherogenic properties. 47,110,125 Exercise also has neuroprotective effects by reducing oxidative stress 126 and promoting mitochondrial biogenesis 127 in the brain.…”
Section: Perspectivementioning
confidence: 99%
“…Cognitive function-related myokines have been demonstrated to regulate the metabolism of not only skeletal muscle but also the brain. A recent review also concluded that molecular mechanisms underlying exercise modulating cognitive performance are expected to be due to up-regulated neurogenesis and synaptic plasticity mediated by myokines [ 20 ].…”
Section: Introductionmentioning
confidence: 99%